Studi Keterampilan Guru Kelas Iv Dalam PengembanganMedia Pembelajaran Kurikulum 2013 Di SDN Gumpang 1Kartasura, Sukoharjo - Dewi, Fatimah Ratna, Dra. Ratnasari Diah Utami, M.Si, M.Pd (2017)
This study aims to determine the skills of teachers in the development of instructional media curriculum in 2013 at the fourth grade students of SDN Gumpang 1 Kartasura, Sukoharjo. This research is a case study. Source data from this study that the principal, teachers, and students to use the techniques of collecting data through interviews, observation, and documentation. This study uses data validity by triangulation and source triangulation techniques. Data were analyzed interactively consisting of data collection, data reduction, data presentation, and data verification. From the research that has been done, it showed 1) teacher in class IV at SDN Gumpang 1 has been designing and creating instructional media from of simple periscope, power point, simple tool light reflection, the main tree, print out a poem, print out the text of story, etc. 2) teacher in class IV at SDN Gumpang 1 have use the medium of learning designed and created themselve and using instant learning media. 3) barriers and solutions in the development of instructional media that lack of training in the development of instructional media curriculum in 2013 so that teachers feel hassles should be designing and creating instructional media, and a solution obtained by principals and teachers SDN Gumpang 1 is to ask for assistance, training, and also follow the activities of KKG time.